Hunan University Campus "Teaching and Research Building Two" Preservation and Reuse Design. Issue 8 (February 2019) - Augelli, Francesco; Li, Yuwei; Liu, Su; Rigamonti, Matteo; Tian, Changqing; Yi, Yu
Abstract: Hunan University Campus is an architecturally and historically relevant academic facility complex set in the city of Changsha, in People's Republic of China Hunan Province. Its modern era masterplan construction started in the 1920s, Teaching and Research Building Two" was the first building finished in 1926. In 2015 has been enlisted in "China Sites of Cultural Relics Protected at National Level" lists. As an international and multidisciplinary team the authors were, with different roles, called to study the building history, define its problems and decay episodes, and design solutions for its preservation and social and functional reactivation. In this scenario the present work will outline the results of the researches done on the building giving a brief overall view but mainly focusing on those aspects that had major impact on many choices in the subsequent phases. Then the general field diagnostic on the building will be presented, focusing again briefly on the general methodologies and results, then getting more specific into those aspects that had major influence in the project part. The design phase will be constituted by two aspects: The Preservation and the Reuse Design. As it might be evident, the first will concentrate on removing the most prominent decay episodes and their causes from the structure, the second will focus on the insertion of new functions and the subsequent user needs to ensure a contemporary life to the building. Apart from these basics it will be though evident that the reuse design strategies that are intended to enhance the user experience are directly connected to the conservation guidelines, trying to trace a common "minimum intervention driven" and "immediate awareness of the contemporary additions in the palimpsest" design strategy that will not hinder the problem solving aims nor the contemporary standards and expectations. In fact these two design aspects, even if presented as separate chapters for better comprehension, will appear as solidly interwoven: the common conservation aim and the firm interdependence of the strategies between the preservation and the reuse project as well as how these strategies are intermixed in the historical palimpsest layers of the building will possibly result as one of the most interesting aspect of this paper, and potentially an interesting case-study in modern building preservation design methodologies panorama.